(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Snakebite poisoning is a public health concern to persons in agrarian environments and Langtang North Local Government Area is not an exception. Agricultural and field workers have been reported to be at higher risk of snakebite in this area. The objective of this paper is to examine the prevalence rate and factors predisposed to snakebite. The primary data was gotten from information drive from questionnaire interview of the respondents (victims) while secondary data was obtained from hospital records at Zamko Comprehensive Health Centre (CHC) and National Population Commission and was analysed by using frequency table and trend line as well as the prevalence rate formula (equation). The results showed that the highest number of snakebites incidence was recorded in 2017 with 117 cases, followed by 2008 and 2018 with 109 cases each. The lowest was recorded in 2014 with 33 cases of snakebites. The result further depicts that the highest number of the snakebite cases was recorded at Zamko ward with 117 cases, followed by Nyer with 100 cases, Lipchok and Kuffen C ward had 78 cases each. The prevalence rate of snakebite cases in Langtang north LGA was found to be 424/100000. The findings of the study shows that majority of the snakebite victims were farmers with 36.23% and was observed from the findings that majority 37.68% of the bites occurred in the morning time as compared to the number in the night with 33.33%. Thus, the major factors found to be associated with snakebites included farming activities